The influence of self-drive on the development of Malay language programme: Non-native adults’ perspective - Muniandy, Punitha Vathi; Othman, Abdul Jalil; Jamaluddin, Sharir (Gyandhara International Academic Publications, 2018)
Purpose: The purpose of the study is to analyse non-native adults’ self-drive and ways that has influenced towards the development of Malay language programme in which the programme caters to their needs, expectations and self-drive in University of Malaya for Continuing Education. Methodology: This study aims to analyse non-native adults’ self-drive in an informal adult education at a higher learning institution in Malaysia using an action research method comprising 58 non-native adult learners which was implemented from January 2014 to December 2017. The evidence gathered through feedback, observation and continuous assessment. Findings: The outcome of this study reveals that strong self-drive among non-native adult learners encouraged and increased the effort towards the introduction of a Malay language programme that suits their needs and expectations. Research Limitations/Implications: It was reported that the development of new Malay programme would have been more successful and benefits more language instructors and academicians. Their involvement would provide more support and critical views in the research in order to validate the formulation of the Malay programme. Social Implications: The improvement in teaching and learning process undertaken has also accelerated adult learners’ attainment and competency in Malay language. As a result of non-native adult leaners’ excellent attainment has reinforced the Malay language educator to attract and increase the enrolment for continuing education at higher learning institutions that offer Malay programme as lifelong learning programme. Originality/Value: The study on self-drive among non-native adults and how it has influenced towards the development of a Malay programme that caters to their needs, interests and expectations is still new, and it is a first-hand study of its kind. The results will be useful for those who are involved in adult teaching and in steering Malay as Modern Foreign Language programme at higher education.